Islamic Criminal Law in Contemporary Academic Discourse: Conceptual and Implementation Challenges - Pramidazzura Alifa Rifqi (Journal of Nafaqah, 2025)
Islamic criminal law remains one of the most contested areas within contemporary legal and academic discourse, particularly regarding its conceptual foundations and feasibility of implementation in modern legal systems. This article examines the conceptual ambiguity and structural challenges surrounding Islamic criminal law by employing a normative juridical approach with statute, conceptual, and case analyses. The study finds that contemporary debates frequently reduce Islamic criminal law to its punitive dimensions, neglecting its jurisprudential foundations rooted in ethical objectives, interpretive reasoning, and procedural restraint. Such reductionism contributes to fragmented academic discourse and directly influences implementation failures in modern state systems. Experiences from jurisdictions such as Aceh and Malaysia demonstrate that the incorporation of Islamic criminal law without methodological adaptation generates legal inconsistency, selective enforcement, and normative conflict. This article argues that the crisis of Islamic criminal law is fundamentally methodological rather than doctrinal. It proposes a prescriptive reconstruction framework grounded in maqāṣid al-sharīʿah, contextual ijtihād, and restorative justice principles to reconcile Islamic criminal law with contemporary legal standards. By repositioning Islamic criminal law as a dynamic and ethically grounded legal tradition, this study contributes to a more coherent and sustainable model of criminal justice reform